وێنە شاراوەکان لێکۆڵینەوەیەکە پشت بە تیورەکانى دواى بونیادگەرى دەبەستێت - كريم, ظاهر لطيف (Sulaimani Journal for Humanities, 2002)
This study comprises the first attempt to examine the theory of poststructuralism in Kurdish literature, and at the same time, Goran's creative ability and stength. Goran, throgh only one verse, could deal, indirectly, many aspects such as: Romantism, Lyricism, the arts of narrative and drama, equlization (balauce of power), literary, Social, historical and imagination experiments.